2021
DOI: 10.1007/s13199-021-00789-x
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic fungi as direct plant growth promoters for sustainable agricultural production

Abstract: Current rates of population growth require the development of new agricultural strategies to feed the world human and livestock. The massive use of agricultural chemicals causes serious damage to the environment, and to human and animal health. For this reason, the use of endophytic fungi represents a biological alternative in increasing agricultural productivity in a sustainable way. This group of microorganisms, which inhabit plant tissues and organs without causing symptoms of damage, includes a great diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
45
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 158 publications
5
45
0
3
Order By: Relevance
“…Compared to rhizosphere soil strains, endophytes can more effectively colonize plants and better adapt to environmental changes, making them more effective in disease suppression and growth promotion [12]. Volatile organic compounds (VOCs) that are produced by endophytic fungi have been used to control plant disease and promote plant growth [13][14][15]. For example, endophytic fungi, isolated from Pelargonium graveolens, Melia azedarach, Chenopodium album, and Malva parviflora, are rich sources of secondary metabolites for use in bio-control [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to rhizosphere soil strains, endophytes can more effectively colonize plants and better adapt to environmental changes, making them more effective in disease suppression and growth promotion [12]. Volatile organic compounds (VOCs) that are produced by endophytic fungi have been used to control plant disease and promote plant growth [13][14][15]. For example, endophytic fungi, isolated from Pelargonium graveolens, Melia azedarach, Chenopodium album, and Malva parviflora, are rich sources of secondary metabolites for use in bio-control [13].…”
Section: Introductionmentioning
confidence: 99%
“…Almeida et al found that endophytes were promising biological control agents because of their antagonistic activity toward the mycelial growth of grapevine trunk diseases (GTD)-associated fungi [16]. Some endophytic fungi can also promote plant growth by increasing plant access to nutrients (nitrogen, phosphorus, potassium, zinc, and iron), producing phytohormones, and increasing plant stress tolerance [14]. Poveda reported that microbial VOCs (MVOCs) were highly beneficial to plants and could be used in agriculture [15]; MVOCs were found to modulate plant and microbial growth, induce plant systemic resistance, and affect insects, nematodes, and other organisms [17].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the mechanisms involved in promoting plant growth and disease protection by means of endophytic fungi include increasing access to nutrients (nitrogen, phosphorus, potassium, zinc, iron, etc. ), the production of antibiotics, the production of plant hormones, a reduction in ethylene, or an increase in water acquisition rate [9].…”
Section: Introductionmentioning
confidence: 99%
“…Trichoderma includes several species widely studied and used as beneficial microorganisms in agriculture, primarily as biological control agents, due to different mechanisms of action, such as mycoparasitism, antibiosis, space and nutrient competition, modulation of plant local and systemic resistance, mediated tolerance to abiotic stresses and plant growth promotion [15]. The ability of Trichoderma to promote plant growth and productivity in crops is a consequence of the production of different secondary metabolites (harzianic acid, 6-pentyl-a-pyrone) and phytohormones (auxins, cytokinins), fully known mechanisms in different endophytic fungi [16]. The ability to promote plant growth and yield has been previously described for Trichoderma in tomato or vineyard crops [17,18].…”
Section: Introductionmentioning
confidence: 99%